Three essays on crime policy and development (2017)
Successful crime control policies are key for economies transitioning towards development. The three chapters in this dissertation aim to evaluate the effects of law enforcement policies as well as characteristics of the prison system on violence, criminal behavior and state legitimacy. In the first chapter I use the allocation of inmates to old and new Colombian prisons to examine the effects of poor prison conditions on recidivism. In the second chapter (with Christopher Blattman, Donald Green and Daniel Ortega) we evaluate the effects of hot spots policing and municipal services on crime, violence and state legitimacy. In the third chapter (with Santiago Gómez and Daniel Mejía) we benefit from a quasi-experimental setting in Medellín, Colombia to evaluate the deterrent effects of public surveillance cameras on criminal behavior.